Adherence to Cancer Survivorship Care Guidelines and Health Care Utilization Patterns Among Nonmetastatic Breast Cancer Survivors in Singapore. (4th March 2022) - Ke, Yu; Tan, Chia Jie; Yeo, Hui Ling Angie; Chan, Alexandre
Abstract : PURPOSE: Currently, limited information is available on care provided to breast cancer survivors in Singapore. This study aims to assess the quality of post-treatment cancer survivorship care among breast cancer survivors on the basis of compliance with international guidelines up to 5 years post-primary treatment. METHODS: This study analyzed a cohort of 189 nonmetastatic breast cancer survivors recruited from the National Cancer Centre Singapore, Changi General Hospital, and KK Women's and Children's Hospital between November 2011 and September 2015. Data were retrieved from electronic medical records in 6-month intervals. Adherence to guidelines was assessed in four areas: (1) recurrent cancer surveillance, (2) monitoring and detecting late effects, (3) health care resource utilization, and (4) preventive care. Descriptive statistics, Kaplan-Meier, and regression analyses were conducted. RESULTS: Annual surveillance mammogram adherence rates were ≥ 83% consistently. The most common new diagnosis was osteoporosis at an incidence rate of 102 (95% CI, 77.6 to 135) cases per 1, 000 person-years. Overall, ≤ 10.1% of survivors had an emergency department or hospitalization visit. Oncologist services were overutilized, with a median of 6 (interquartile range: 4-10) visits in the first 6 months before reducing to a median of 2 (interquartile range: 1-3) visits biannually 3 years post-treatment. Bone mineral density test utilization rate adhered to guidelines for 92.2% of aromatase inhibitor recipients but only for 36.4% of premenopausal tamoxifen recipients. CONCLUSION: Overall, adherence rates to surveillance and osteoporosis preventive care were high. Extensive utilization of oncologist services up to 5 years post-primary treatment could be reversed with strategies to engage and coordinate survivorship care with primary care providers, leveraging their strengths to improve adherence to health promotion and chronic disease management. Abstract :